Penerapan Sigalovada Sutta Terhadap Character Building Pada Mahasiswa Stab Maha Prajna Pasca Pandemi - Suparman; Bondan Ade Prasetya (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya Wonogiri, 2025)
Educating adolescents is a planned effort to develop students' potential and shape their character, so they become individuals who are beneficial to themselves and their environment. The current era of globalization influences the character of adolescents, with issues emerging in society such as violence perpetrated by adolescents, free sexual relations, fights among students, free association, and alcohol consumption. In Buddhism, the education taught by the Buddha to the youth Sigala in the Sigalovada Sutta becomes a foundation for building good attitudes and behaviors. The instillation of character values in that sacred text is expected to change the attitudes and behaviors of today's adolescents. The character values instilled include responsibility, discipline, hard work, friendship, tolerance, peace, and religiosity. The method used in this research is descriptive qualitative. The result of the study in this article is to form a better character and personality and easily adapt to the environment through understanding the character values contained in the sigalovada sutta and education in Buddhism.